2013
DOI: 10.1186/1471-2458-13-735
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of HIV self-testing: a systematic literature review

Abstract: BackgroundThe uptake of HIV testing and counselling services remains low in risk groups around the world. Fear of stigmatisation, discrimination and breach of confidentiality results in low service usage among risk groups. HIV self-testing (HST) is a confidential HIV testing option that enables people to find out their status in the privacy of their homes. We evaluated the acceptability of HST and the benefits and challenges linked to the introduction of HST.MethodsA literature review was conducted on the acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
240
4
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(274 citation statements)
references
References 45 publications
27
240
4
3
Order By: Relevance
“…These findings are consistent with previous study findings that have found HIV testing to be acceptable among various populations, demonstrating the potential of HIVST as a strategy that may improve access to HIV testing [3].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with previous study findings that have found HIV testing to be acceptable among various populations, demonstrating the potential of HIVST as a strategy that may improve access to HIV testing [3].…”
Section: Discussionsupporting
confidence: 92%
“…A review of 11 studies across different contexts suggested HIVST has high acceptability in most instances and increases the reach of HIV testing services with users capable of providing accurate results [3]. Data indicating user preference for oral or blood rapid tests are weak; however, users generally have more difficulty performing blood-based rapid tests [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…As such, they must meet minimum performance standards, and diagnoses are made only through validated, multi-test algorithms [2,7]. Nevertheless, benefits of HIVST within specific settings and populations have now been documented in literature reviews [8][9][10], pilot studies [11][12][13], meeting reports [14], technical updates [15], and interim data and research [16][17][18].…”
mentioning
confidence: 99%
“…Importantly, non-invasive options for specimen collection, such as saliva-based tests, can facilitate access to and acceptability of HIV testing [13]. Peer outreach activities have demonstrated to be effective in some countries, and income levels have increased the usage of HIV testing among key populations, such as MSM and individuals engaged in SW.…”
Section: Introductionmentioning
confidence: 99%